Novos compostos de coordenação de Fe(III) e Co(III) contendo os ligantes triazinana e tiabendazol e o estudo de suas ações antitumorais - Senra, Carina Aparecida dos Santos (2016)
New Iron (III) and cobalt (III) coordintation compunds with triazinane and thiabendazole ligands were synthesized, characterized and their antitumor activities were tested. The obtained compounds were characterized by several tecniques in order to elucidate their structures and molecular formules, such as: infrared electronic spectroscopy, mass spectrometry, ultraviolet-visible electronic spectroscopy, thermal analysis, Mössbauer, elemental analysis, and hydrogen nuclear magnetic resonance. The compounds exhibited the following molecular formules: Na6(Fe2TRZ4), Na(FeTRZ).H2O.Fe(OH)3, (FeTBZ2Cl2)Cl, Na4(FeTRZCl4).3H2O. Cytotoxic activity of the complexes was evaluated against 4 tumor cell lines: Human hepatocellular carcinoma HepG2 (ATCC® ™ HB 8065), human breast cancer MCF-7 (ATCC® HTB-22), human pancreatic cancer MiaPaCa-2 (ATCC ® ™ CRL-1420) and Hepa 1c1c7 murine hepatocellular carcinoma (ATCC® CRL-2026 ™) by two types of tests: screening and MTT colorimetric assay. According to these tests, triazinane compound only showed antitumor activities: Fe (III) complex demonstrated significant antitumor activity against all tested cell lines; Co (III) exhibited antitumor activity only against HEPA 1c1c7 cell. In conclusion, this work led to 4 new compounds, and two of then were antitumor active.